1997
DOI: 10.1152/ajpgi.1997.272.3.g597
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins induce proliferation of rat hepatocytes through a prostaglandin E2 receptor EP3 subtype

Abstract: We characterized the proliferative action of prostaglandins (PGs) in relation to their membrane receptors on rat hepatocytes in primary culture. PGs in the order 16,16-dimethyl PGE2 > PGE2 > PGF2alpha >> PGD2 augmented epidermal growth factor (EGF)/insulin-induced DNA synthesis, assessed by [(3)H]thymidine incorporation, in a concentration-dependent manner, whereas PGs alone did not stimulate basal DNA synthesis without EGF and insulin. The cells exhibited [(3)H]PGE2 binding sites that were displaced by unlabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
3
23
2
1
Order By: Relevance
“…Taken together, our results suggest that, although a minor effect is exerted by FP receptors, EP3 receptors mediate most of the growth stimulatory effects of prostaglandins in hepatocytes. Thus, we have confirmed the involvement of EP3 receptors as described by Hashimoto et al (1997); however, we could not detect a significant contribution from EP1 receptors (Kimura et al, 2001). …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Taken together, our results suggest that, although a minor effect is exerted by FP receptors, EP3 receptors mediate most of the growth stimulatory effects of prostaglandins in hepatocytes. Thus, we have confirmed the involvement of EP3 receptors as described by Hashimoto et al (1997); however, we could not detect a significant contribution from EP1 receptors (Kimura et al, 2001). …”
Section: Discussionsupporting
confidence: 71%
“…Subsequent studies have suggested that G i may exert an effect on hepatocyte DNA synthesis downstream of receptor coupling . In other studies, growth enhancement induced by prostaglandins in hepatocytes has been attributed to EP3 (Hashimoto et al, 1997) and EP1 receptors (Kimura et al, 2001), respectively. The aim of the present study was to further elucidate the role of the different prostaglandin receptors in growth enhancement, using receptor-selective agonists and antagonists.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, evidence indicates that PGs promote cell proliferation, and conversely the growth-inhibitory effects of COX inhibitors can be reversed by exogenous addition of PGs. It has been demonstrated that prostaglandins increase DNA synthesis and cell proliferation of rat hepatocytes [68,69] , and of human HCC cells [45] . On the other hand, it has been demonstrated that COX-2 inhibitors are able to suppress HCC cell growth [44,45,58,[70][71][72][73][74] .…”
Section: Cox Inhibitors In Hepatocellular Carcinomamentioning
confidence: 99%
“…Several studies have suggested the role of PGE 2 receptors in cellular proliferation and tumor development. The EP 3 subtype PGE 2 receptor is responsible for the proliferative effect of PGs on rat hepatocytes (16). Experiments on EP 1 -deficient mice show that this subtype receptor is required for the development of preneoplastic lesions induced in colon epithelium by the carcinogen azoxymethane (56).…”
mentioning
confidence: 99%